2020
DOI: 10.1111/ejn.14712
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the understanding of the aetiology and therapeutic strategies in burning mouth syndrome: Focus on the actions of cannabinoids

Abstract: Burning mouth syndrome (BMS) is a neuropathic pain disorder associated with a burning sensation on oral mucosal surfaces with frequently reported xerostomia, dysgeusia and tingling or paraesthetic sensations. However, patients present no clinically evident causative lesions. The poor classification of the disorder has resulted in a diagnostic challenge, particularly for the clinician/dentist evaluating these individuals. Major research developments have been made in the BMS field in recent years to address thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 178 publications
0
23
0
1
Order By: Relevance
“…Patients affected by NCP are considered to be at high risk to develop a cognitive decline, especially in the domains of attention, working memory, and executive functions (Moriarty et al, 2011;Moriarty and Finn, 2014), which leads to the poor quality of life, difficulty in adherence to medications, increasing the risk of mortality, and health resource utilization (O'Connor, 2009;Colloca et al, 2017). Burning mouth syndrome is a complex chronic orofacial pain disorder frequently associated with several psychiatric comorbidities such as anxiety, depression, and sleep disturbances (Kim et al, 2020;Pereira et al, 2020) while CI have never been evaluated in a complete way. Only one study is found in the literature by Kim et al (2020), in an observational but a retrospective study, suggested that patients with BMS were not associated with an increase in the incidence of dementia and Parkinson's disease based on the diagnosis performed in ∼10 years by physicians, moreover, they could not assess whether the development of both conditions may be the consequence or were involved in the onset of BMS (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients affected by NCP are considered to be at high risk to develop a cognitive decline, especially in the domains of attention, working memory, and executive functions (Moriarty et al, 2011;Moriarty and Finn, 2014), which leads to the poor quality of life, difficulty in adherence to medications, increasing the risk of mortality, and health resource utilization (O'Connor, 2009;Colloca et al, 2017). Burning mouth syndrome is a complex chronic orofacial pain disorder frequently associated with several psychiatric comorbidities such as anxiety, depression, and sleep disturbances (Kim et al, 2020;Pereira et al, 2020) while CI have never been evaluated in a complete way. Only one study is found in the literature by Kim et al (2020), in an observational but a retrospective study, suggested that patients with BMS were not associated with an increase in the incidence of dementia and Parkinson's disease based on the diagnosis performed in ∼10 years by physicians, moreover, they could not assess whether the development of both conditions may be the consequence or were involved in the onset of BMS (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Burning mouth syndrome is a complex chronic orofacial pain disorder frequently associated with several psychiatric comorbidities such as anxiety, depression, and sleep disturbances (Kim et al, 2020 ; Pereira et al, 2020 ) while CI have never been evaluated in a complete way. Only one study is found in the literature by Kim et al ( 2020 ), in an observational but a retrospective study, suggested that patients with BMS were not associated with an increase in the incidence of dementia and Parkinson's disease based on the diagnosis performed in ~10 years by physicians, moreover, they could not assess whether the development of both conditions may be the consequence or were involved in the onset of BMS (Kim et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a large body of data suggest that cannabinoids have therapeutic properties, alleviating symptoms of several CNS disorders. Indeed, cannabinoids can mitigate inflammation, reduce CNS spasticity, alleviate neuropathic pain, and a body of evidence indicates that cannabinoids provide neuroprotection following injury or inflammation in the CNS [ 99 , 100 ]. The most well-known cannabinoids are the phytocannabinoids synthesized by C. sativa , including THC, a euphoric component of the plant, in addition to CBD, cannabinol (CBN), cannabichromene (CBC) and cannabigerol (CBG), which are considered non-euphoric cannabinoids [ 101 ].…”
Section: Cannabinoidsmentioning
confidence: 99%
“…Currently, BMS is considered a multifactorial disease in which a central brain dysfunction (Hagelberg et al., 2003; Khan, Keaser, Meiller, & Seminowicz, 2014), a peripheral small fiber neuropathy (Lauria, 2005; Yilmaz et al., 2007), and psychological (Galli, Lodi, Sardella, & Vegni, 2017; Kim & Kho, 2018) and inflammatory factors ( Barry, O'Halloran, McKenna, McCreary, & Downer, 2018; Pereira et al., 2020) have been reported in its etiopathogenesis. In the last International Classification of Orofacial Pain, the authors captured the multidimensionality of the pain, highlighting the important role of social and psychological factors (the biopsychosocial model) in the assessment and management of every type of orofacial pain (ICOP, 2020).…”
Section: Introductionmentioning
confidence: 99%